Literasi Keuangan Islam, Kesiapan Teknologi, dan Komitmen Religius: Penentu Adopsi Fintech pada Kalangan Dewasa Muda di Indonesia - Tiara Dwitiya Said; Goso Goso; Yusuf Kamaruddin (Universitas Nusantara PGRI Kediri, 2026)
Indonesia is a country with the largest Muslim population and high internet penetration, but the number of young adults using Islamic fintech remains low at 23%. To predict the adoption of Islamic fintech by young Indonesian adults, this study developed and tested the Islamic Technology Acceptance Model (I-TAM). Data were collected from 400 Muslim respondents aged 18 to 35 years old through a structured questionnaire. A cross-sectional survey design was used using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that technological readiness was the strongest predictor of Islamic fintech adoption (β=0.522, p<0.001), followed by Islamic financial literacy (β=0.330, p<0.001), and religious commitment (β=0.103, p<0.001). A key finding is that the dual moderating role of religious commitment weakens the effect of Islamic financial literacy (β=-0.147, p=0.008) but strengthens the effect of technological readiness (β=0.190, p<0.001). More than the conventional TAM model, the I-TAM model explains 58.4% of Islamic fintech adoption. This study suggests that for young Indonesian Muslims, religiosity and technological modernity can coexist well, with technology serving as a means of practicing religious values ​​in the technological era.